The Influence of Leadership, Work–Life Balance, and Work Environment on Employee Performance at Puskesmas Mandai, Indonesia - Sela Mita Permatasari; Baso Amang; Ilham Labbase (Pustaka Digital Indonesia, 2026)
In the context of increasing demands for healthcare service quality, improving employee performance has become a critical priority for public health institutions, particularly at the primary care level. However, limited attention has been given to how leadership, work–life balance, and work environment jointly relate to employee performance in public health centers. This study aims to examine the association between leadership, work–life balance, work environment, and employee performance at Mandai Public Health Center (Puskesmas Mandai), Maros Regency. A quantitative cross-sectional survey was conducted from December 2025 to January 2026 involving all 93 employees. Data were collected through structured questionnaires and analyzed using descriptive statistics and multiple linear regression. The results show that leadership was positively and significantly associated with employee performance (B = 0.317; t = 4.948; p < 0.05). Work–life balance was also positively and significantly associated with employee performance (B = 0.440; t = 11.025; p < 0.05), while work environment showed a positive and significant association with employee performance (B = 0.181; t = 2.579; p < 0.05). The simultaneous test confirmed that the three variables jointly predicted employee performance, F(3, 89) = 158.325; p < 0.05, with strong explanatory power (R² = 0.842). Theoretically, this study contributes by showing that employee performance in a primary healthcare context is related to the alignment of organizational leadership, workplace support, and employees’ ability to manage work and personal demands. Practically, Mandai Public Health Center may benefit from more predictable scheduling, fair workload distribution, clearer leadership communication, and improvements in service-supporting workplace facilities.